The impact of a rural or urban context in eating awareness and self‐regulation strategies in children and adolescents from eight European countries. (24th March 2014) - Gaspar, Tania; de Matos, Margarida Gaspar; Luszczynska, Aleksandra; Baban, Adriana; Wit, John
Abstract Complex relationships exist between eating behaviour and personal and environmental factors. Rural and urban geographic contexts seem to play a role in eating behaviour, and therefore deserve a deeper study. A healthy eating behaviour and the conditions that promote it are a major issue in the promotion of adolescent health. The study aims to investigate the associations between the area of residence (urban vs. rural), self‐regulation strategies (TESQ‐E) and eating behaviours among children and adolescents. A total of 11, 820 adolescents (50.6% girls) participated in the study, with a mean age of 13.30 years (SD= 2.13). Nine countries (The Netherlands, United Kingdom, Poland, Portugal, Denmark, Romania, Germany, Finland and Belgium) completed a questionnaire in the school context, asking about the use of self‐regulation strategies, eating behaviour awareness/care and sociodemographic questions such as age, gender and residential area. Both areas of residence (urban vs. rural) are associated with eating awareness/care in Romania and Portugal, controlling for age, gender and self‐regulation strategies. In some European countries at least, and most probably around the world, health promotion should focus on an ecological approach that includes the understanding of the effect of both environmental factors and personal skills on eating behaviour/awareness.